Ruth Phipps letter to Nicholas S. Halmi regarding bird watching, February 5, 1978 - Phipps, Ruth O.et al (1978)
Letter from Ruth Phipps to Nicholas S. Halmi, regarding bird watching, February 5, 1978. Sightings of Loggerhead Shrikes, Evening Grosbeaks, Common Redpolls, and a Harlan's Hawk are noted. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter, 1977-1978. Epson - sheet feed/flatbed